Implementation of Islamic-Based Character Education at Bina Insania Arrahman PAUD, Ternate City - Delvi Samsudin; Miranti Hamid; Nabila Ilham; Nurfitri Sahidun (Golden Ratio of Social Science and Education, 2026)
This study aims to describe the implementation of Islamic-based character education at PAUD Bina Insania Arrahman in Ternate City, with a focus on the form of implementation, the process of internalizing character values in early childhood, and the role of teachers and the school environment in the formation of Islamic character. This study used a qualitative approach with descriptive research. The research subjects included the principal, teachers, and parents of students who were selected purposively. Data collection techniques included in-depth interviews, observations, and documentation. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions, while the validity of the data was guaranteed through triangulation of sources and techniques. The results of the study indicate that Islam-based character education is implemented in an integrated manner through religious habits, teacher role models, and an Islamic-nuanced school culture. The process of internalizing character values takes place gradually through consistent introduction, habituation, and reinforcement according to the developmental stages of early childhood. Teachers and the school environment play a key role in the success of Islamic character formation, with parental support as a reinforcement of values in the family environment. This study confirms that Islamic-based character education in early childhood is an ongoing process that requires synergy between schools and families.